توكيل ولي النكاح عند عقد النكاح (دراسة حالة: فهم الولي بقرية جنطيني لارن لامونجان في أركان النكاح) إعداد: محمد نصوحا،المشرف الأول: عيسى أنصاري الماجستر، المشرف الثاني:عبد الباسط الماجستر. - Mohammad Nasucha; Isa Anshori; Abdul Basith (MAQASID, 2020)
Abstract :Guardian is one of the pillars in a marriage, because the position of the guardian is a legal and whether a marriage determinant. However, some trustees understand that the position of guardians is only used as a formality. So that many trustees are still found to represent their guardianship rights to the Penghulu. This is the case, in Centini Village, Laren Subdistrict, Lamongan Regency, many marriage guardians choose someone else to be their guardian on the marriage covenant, although there is no obstacle for the representatives to marry off their daughter on the marriage covenant.From this background, the writer formulates the problem into 2, namely 1) How is the understanding of guardians in Centini Village, Laren Subdistrict, Lamongan Regency, regarding Tauki>l Waly nikah in a marriage covenant? 2) What are the reasons for the marriage guardian in doing Tauki>l Waly ?. This type of research is field research because researchers observe directly what is happening in the community. This research uses descriptive qualitative normative analysis method in presenting the results of research using words based on data obtained. The data collection method is obtained through observation, interviews and documentation.Centini Laren Subdistrict Lamongan Regency has an understanding that Tauki>l Waly nikah is allowed. Their understanding is only based on the many practices of Tauki>l Waly in Centini Village which are carried out by the marriage guardian in each marriage procession. Nevertheless, they agreed that the guardian was a harmonious marriage covenant and was a virtue for the guardian if he allowed his own child getting married. The factors that became the reason for the marriage guardian in doing Tauki>l Waly were 1) The assumption of the trustees that marriage is the duty of the Office of Religious Affairs officers, while the guardian is only looking for a partner for his child. 2) Fear that mistakes occur when Ijab in a marriage covenant. 3) Tauki>l Waly becomes a custom for marriage guardians. Keywords: Guardians’ Understanding, Tauki>l Waly, Marriage Covenan